2012
DOI: 10.1016/j.cell.2011.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Immune Surveillance and Therapy of Lymphomas Driven by Epstein-Barr Virus Protein LMP1 in a Mouse Model

Abstract: SUMMARY B cells infected by Epstein-Barr-Virus (EBV), a transforming virus endemic in humans, are rapidly cleared by the immune system, but some cells harboring the virus persist for life. Under conditions of immunosuppression EBV can spread from these cells and cause life threatening pathologies. We have generated mice expressing the transforming EBV latent membrane protein 1 (LMP1), mimicking a constitutively active CD40 coreceptor, specifically in B cells. Like human EBV infected cells, LMP1+ B cells were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
171
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(186 citation statements)
references
References 53 publications
11
171
0
1
Order By: Relevance
“…None of these targets were killed by T cells isolated from CD19-Cre ERT2 ; hCD2 flSTOP mice 8 d after tamoxifen treatment. These results indicate that the activated CD8 T cells kill LMP-driven B-cell blasts in an antigen-specific, MHCrestricted manner in line with our earlier data on T-cell surveillance of LMP1-induced B-cell lymphomas in the mouse (21) and data from the human (25).…”
Section: Reviewerssupporting
confidence: 77%
See 2 more Smart Citations
“…None of these targets were killed by T cells isolated from CD19-Cre ERT2 ; hCD2 flSTOP mice 8 d after tamoxifen treatment. These results indicate that the activated CD8 T cells kill LMP-driven B-cell blasts in an antigen-specific, MHCrestricted manner in line with our earlier data on T-cell surveillance of LMP1-induced B-cell lymphomas in the mouse (21) and data from the human (25).…”
Section: Reviewerssupporting
confidence: 77%
“…Conditional expression of LMP2A in mouse GC B cells disturbs affinity maturation and leads to lupus-like symptoms in aged mice (23). More recent studies, in which LMP1 was conditionally expressed in mouse B cells, showed that this single EBV protein is sufficient to provide B cells with the ability to elicit tight T-cell immunosurveillance and, in the absence of immunosurveillance, to proliferate and eventually give rise to B-cell lymphomas (21,22). Although earlier in vivo studies have offered insights into the role of LMP1 as an oncogene and of LMP2A as a BCR surrogate, little attention has been paid to the immune response against LMP-expressing B cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental models have shown a central role for CD8 + T cells in protective immunity to EBV. 15,16 Longitudinal analyses of lymphocyte cytotoxicity in the patient demonstrated an absence of exocytosis and cytotoxicity by both CTL and NK cells ( Figure 3B,C), which was partially restored by IL-2 stimulation ( Figure 3D,E). Relative to a healthy control, EBV-specific T cells in the patient produced TNF-α, but displayed impaired degranulation in response to BZLF-1 peptides ( Figure 3F).…”
Section: Resultsmentioning
confidence: 98%
“…Together with LMP1, which constitutively activates CD40 signaling (19,20), LMP2A may provide a survival advantage for EBV-infected B cells by modifying GC B-cell selection. However, B-lineage-specific expression of LMP1 inhibits GC formation (20) or causes B-cell ablation through immune surveillance (21). LMP2A does not affect affinity maturation of B cells in GCs when expressed in B cells of a transgenic mouse line (22).…”
mentioning
confidence: 99%